Effects of fractional-order PI controller on delay margin in single-area delayed load frequency control systems - Celik, Vedat; Ozdemir, Mahmut Temel; Lee, Kwang Y. (Ieee-Inst Electrical Electronics Engineers Inc, 2019)
This study aims to determine the improvement effect on the delay margin if fractional-order proportional integral (PI) controller is used in the control of a single-area delayed load frequency control (LFC)system. The delay margin of the system with fractional-order PI control has been obtained for various fractional integral orders and the effect of them has been shown on the delay margin as a third controller parameter. Furthermore, the stability of the system that is either under or over the delay margin is examined by generalized modified Mikhailov criterion. The stability results obtained have been confirmed numerically in time domain. It is demonstrated that the proposed controller for delayed LFC system provides more flexibility on delay margin according to integer-order PI controller.
Keywords: Delay dependent stability; Delay margin; Fractional-order proportional integral (PI); Generalized modified Mikhailov criterion; Load frequency control with delay